2016
DOI: 10.17554/j.issn.2412-2424.2016.02.15
|View full text |Cite
|
Sign up to set email alerts
|

HLA Loci and Respiratory Infectious Diseases

Abstract: The HLA system harbour a wide set of genes that plays an important role in the regulation and action of the immune system against invading pathogens, making them natural candidates for research on the genetic susceptibility for respiratory infections. Thus, along past decades, this topic has been subject to intense research and, consequently, several alleles of those loci have been implicated in the ability, more or less effective, to tackle and control invading pathogens in the respiratory system. Current edi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 124 publications
0
12
0
Order By: Relevance
“…Numerous studies have revealed the existence of significant associations between certain HLA alleles and the susceptibility and prognosis of different infectious diseases [ 22 , 23 ]. HLA includes a large set of genes with important actions in regulation and activity of the immune system against viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed the existence of significant associations between certain HLA alleles and the susceptibility and prognosis of different infectious diseases [ 22 , 23 ]. HLA includes a large set of genes with important actions in regulation and activity of the immune system against viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…In selecting the concerned immunogen, S1 and the S2 domains of the surface glycoprotein have been utilized separately keeping in mind the limitations associated with utilizing the entire surface glycoprotein [71,72]. The prediction of the three different types of epitopes ( B cells, T HTL and T CTL ) by utilizing multiple different servers in each case based on different algorithms and selection based on a consensus involving all the servers including experimental basis behind alleles (HLA Class I and Class II) selected helps add sustenance to the concluded list of epitopes [73][74][75][76][77]. Each of the predicted epitopes were verified based on described parameters and were found to be antigenic, non-allergen, non-toxic and share high coverage across the spike glycoprotein of SARS-CoV-2 sequences [38].…”
Section: Discussionmentioning
confidence: 99%
“…The sequences predicted were matched with the data generated by [73] through IEDB on significant epitopes present on the surface glycoprotein which did mention the need for analysis of the predicted sites and hence the utility of the stringent filters over the different servers followed by validation. The utilization of specific alleles which have been identified in previous manifestation of the SARS CoV has helped us sort the predicted T cell epitopes appropriately on the different servers which otherwise would have made prediction biased [74][75][76][77]. The selected epitopes are listed in Table 1.…”
Section: Prediction Of B Cell T Htl and T Ctl Epitopesmentioning
confidence: 99%
“…Many of respiratory illnesses are the result of bacterial or viral infection of the lungs. Because people were constantly being exposed to harmful bacteria and viruses in their environment, their respiratory health can be adversely affected [3]. There are number of diseases that can cause problems with breathing.…”
Section: Introductionmentioning
confidence: 99%